Transient analysis of laminated composite plates using NURBS-based isogeometric analysis - Nguyen, Lieu B.; Thai, Chien H.; Dang, Ngon T.; Nguyen-Xuan, H. (Vietnam Journal of Mechanics, 2014)
We further study isogeometric approach for response analysis of laminated composite plates using the higher-order shear deformation theory. The present theory is derived from the classical plate theory (CPT) and the shear stress free surface conditions are naturally satisfied. Therefore, shear correction factors are not required. Galerkin weak form of response analysis model for laminated composite plates is used to obtain the discrete system of equations. It can be solved by isogeometric approach based on the non-uniform rational B-splines (NURBS) basic functions. Some numerical examples of the laminated composite plates under various dynamic loads, fiber orientations and lay-up numbers are provided. The accuracy and reliability of the proposed method is verified by comparing with analytical solutions, numerical solutions and results from Ansys software.